Pemanfaatan Teknologi Telekomunikasi dan Internet dalam Meningkatkan Kualitas Pembelajaran pada Lembaga Pendidikan di Era Digital - Sari, Erma; Listyo Prabowo, Sugeng (Lembaga Intelektual Muda (LIM) Maluku, 2026)
The development of telecommunications and internet technology has transformed the world of education, particularly in improving the quality of learning in the digital era. This study aims to analyze the contribution of these technologies to improving the accessibility, personalization, and effectiveness of learning in educational institutions. The research method used a systematic literature review with subjects consisting of scientific articles and academic documents related to digital learning. Data were collected through searches of national and international journal databases, then analyzed using thematic analysis to identify patterns, trends, and research gaps and formulate strategic recommendations. The results show that the use of Learning Management Systems (LMS), video conferencing applications, Massive Open Online Courses (MOOCs), and mobile learning can increase student engagement by up to 65% and learning accessibility by up to 78%. However, challenges such as the digital divide in remote areas and educator readiness in technology integration still require attention. This study recommends a holistic approach through strengthening infrastructure, improving educator competency, and developing digital pedagogy to optimize learning quality.